Nitrogen metabolism in photosynthetic bacteria wastewater treatment: A novel nitrogen transformation pathway. (December 2019) - Yang, Anqi; Zhang, Guangming; Meng, Fan; Zhi, Ran; Zhang, Panyue; Zhu, Yichun
Graphical abstract: Highlights: PSB can efficiently utilize NH4 + -N, NO3 -N and NO2 -N to grow with no preference. Over 90% nitrogen removal efficiencies were obtained under suitable condition. 35 ~ 51% of removed nitrogen was transformed to gaseous nitrogen. Basically no mutual transformation occurred between NH4 + -N, NO2 -N and NO3 -N. Key functional genes for NH4 + -N oxidation could not be amplified in PSB. Abstract: Nitrogen removal from wastewater is a worldwide environmental problem. Photosynthetic bacteria (PSB) were reported to have a great potential in treating varieties of nitrogen-contaminated wastewater. However, their nitrogen metabolic mechanism is still unclear, which was further explored in this work. The results showed that PSB can efficiently utilize NH4 + -N, NO3 − -N and NO2 − -N. Over 90% nitrogen removal efficiencies were obtained under suitable condition. 35 ~ 51% of removed nitrogen was transformed to N2 and N2 O. In addition, basically no mutual transformation occurred between NH4 + -N, NO3 − -N and NO2 − -N in PSB, which is different from other biological technologies. Combining with the analysis of functional gene groups, it indicated that there might be a new direct nitrogen transformation pathway, i.e. NH4 + might be directly oxidized to N2 /N2 O in nitrogen metabolism of PSB, which breaks the limitations of existing technologies, and proposed a new understanding of nitrogen metabolism in PSB.